La place de l’agriculture dans la métropole verte - Roland Vidal; André Fleury (Projets de Paysage)
The frequent confusion between nature and agriculture, and the fact that agriculture is rarely taken into consideration in the modern economic reality, explain that territory projects, at urban region level, are still fluctuating between utopia and realism. However, the recent evolutions, notably observed in Ile-de-France, indicate that the « agri-urban» projects, co-developed between actors from urban and rural fields, will find more and more their place within the « green metropolis». However, this co-development will require the training of professional actors, which should lead to the de-compartmentalization of the academic disciplines in order to sensitize the professionals of urbanism to the agriculture field and reciprocally. This article will address these issues and challenge these new pedagogical perspectives.